KEPEMIMPINAN DALAM PERUBAHAN ORGANISASI PERPUSTAKAAN PERGURUAN TINGGI - Khilal Syauqy (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
Success in the organizational change is determined by leadeship, because leadership with leader is who implementing and planning change. This paper is aimed at obtaining information to related the effect of leadeship with many aspeks on organizational change. Based on those teories reveals that some aspecs of leadersip with (1) visionary leader, (2) comunicator leader, (3) leader as change agent, (4) (leader as coach) and leader as Technology information analysis,could be enhanced and improved organizational change. Therefore this aspecs can be used for achieved organizational change special at University libraries.